THE EFFECTS OF WORKLOAD, WORK ENVIRONMENT, AND JOB STRESS ON EMPLOYEE PERFORMANCE - Burhanudin; Muhammad Febrian Catur HY. (International Journal of Accounting, Management, Economics and Social Sciences (IJAMESC), 2026)
This study aims to examine the effect of workload on employee performance, to examine the effect of work environment on employee performance, and to examine the effect of work stress on employee performance. The sample in this study was 56 employees of Bank BPD DIY Piyungan Branch Office, Bantul, Special Region of Yogyakarta. The data collection technique used a questionnaire, while the data analysis technique used multiple regression analysis. The results of the study found that workload has a negative effect on employee performance, indicating that excessive workload reduces employees' ability to complete tasks effectively and efficiently. Furthermore, the work environment has a positive effect on employee performance, suggesting that a comfortable, supportive, and safe workplace enhances employee motivation, satisfaction, and productivity. In addition, work stress has a negative effect on employee performance, meaning that high levels of stress experienced by employees lead to decreased concentration, fatigue, and lower quality of work output. These findings highlight the importance of managing workload appropriately, creating a conducive work environment, and implementing stress management programs to maintain and improve employee performance. The study contributes to the understanding of how organizational factors influence employee outcomes and provides practical implications for bank management to optimize human resource practices. Future research is recommended to explore additional variables and expand the sample to other banking institutions for broader generalization.